LAW ENFORCEMENT AGAINST DRIVERS WHO DO NOT REPORT CHANGE OF OWNERSHIP - Dony, Mulian; Asnawi, Eddy; Oktapani, Silm (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The assignment of Vehicle Registration Numbers (Tanda Nomor Kendaraan Bermotor - TNKB) serves a purpose and represents one of the initial steps in implementing the legal norms that society aims to achieve. Therefore, as citizens, it is our duty to comply with prevailing laws and regulations. Consequently, every motor vehicle must display a TNKB that adheres to the applicable provisions to ensure compliance with legal norms and regulations. The Indonesian National Police (Kepolisian Republik Indonesia) is the authority responsible for law enforcement, particularly concerning traffic. Traffic and road transportation must be developed to enhance their potential and role in ensuring security, welfare, and order in traffic and transportation, supporting economic development, advancements in science and technology, regional autonomy, and accountability in state administration. This study employs a sociological legal research method. Based on the research findings, law enforcement against drivers who fail to report changes in vehicle ownership in Pekanbaru City, as stipulated in the Chief of the Indonesian National Police Regulation Number 7 of 2021 on Vehicle Registration and Identification, has not been effectively implemented. This is due to the presence of drivers who neglect to report changes in vehicle ownership. Strict law enforcement against non-compliance aims to prevent potential misuse of vehicles, such as theft or fraud, and to ensure the legitimate identification of vehicle owners. Furthermore, law enforcement ensures that vehicles operating on public roads remain properly registered in the vehicle administration system, which is crucial for ownership and tax obligation. The factors hindering law enforcement against drivers who fail to report changes in vehicle ownership in Pekanbaru City, as outlined in the Chief of the Indonesian National Police Regulation Number 7 of 2021 on Vehicle Registration and Identification, include a lack of public awareness about the importance of reporting changes in vehicle ownership, inadequate coordination between law enforcement and relevant agencies in monitoring the ownership change process, as the reporting procedure often involves various administrative stages requiring validation from multiple parties, such as the Regional Revenue Office for vehicle tax payments. Additionally, insufficient oversight of motor vehicle sales transactions, especially those conducted without official documentation, has resulted in many vehicles changing hands without undergoing proper reporting processes. Efforts to address the obstacles to law enforcement against drivers who fail to report changes in vehicle ownership in Pekanbaru City, as per the Chief of the Indonesian National Police Regulation Number 7 of 2021 on Vehicle Registration and Identification, include enhancing public awareness of the importance of compliance with this regulation, imposing sanctions on drivers who fail to report ownership changes to create a deterrent effect and encourage compliance, and providing more intensive education to the public about the legal risks of failing to report vehicle ownership changes. Additionally, the police should develop a more practical and efficient reporting system, such as a digital application that allows the public to report vehicle ownership changes without having to visit police stations.